Epidemiological aspects of gastric cancer in Urnguay - Musé, I; Viola, A. (Cirugía del Uruguay, 1988)
Oncological pathology as a whole constitutes, as already indicated in other publications (1), an important factor as a cause of mortality. In order to In 1986, cancer mortality accounted for 23.2% of total deaths, occupying the second place, after cardiocirculatory affections